Peran Keluarga Dalam Membangun Karakter Anak Usia Dini - Ahmad, Ery Subaeri (Al-Wasathiyah: Journal of Islamic Studies, 2022)
Character education is a way to make Indonesian children and society have commendable and civilized moral behavior. Therefore, the discourse of character education continues to be activated in every school to build the noble character of students. But in reality, there are still school children who do not have noble character. One of the contributing factors is the lack of basic morals instilled by parents in the child's self and soul. Building character in children, especially early childhood is not as easy as turning the palm of the hand. We must be very careful because early childhood is a critical period in character education. The behaviors that children acquire and learn at this age will be difficult to change and will continue to carry over until the child grows up. The role of parents is very necessary in this case. Because parents are the first to interact with children as well as the main educators for children who are at an early age. The things that parents teach at an early age will form the basis of the child's character and will continue to carry over until he grows up. Therefore, parents must teach good things to their children and provide a strong basis for character and morality to their children.